2012
DOI: 10.1128/jcm.06817-11
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Multiplex PCR for Detecting Shiga Toxin 2-Producing Escherichia coli O104:H4 in Human Stools

Abstract: A real-time multiplex PCR targeting stx 2 , wzy O104 , and fliC H4 of enterohemorrhagic Escherichia coli (EHEC) O104:H4 correctly determined the presence or absence of these genes in 253 EHEC isolates and enrichment cultures of stool samples from 132 patients. It is a rapid, sensitive, and specific tool for detecting EHEC O104:H4 in human stools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…A limitation of the two pooled NAAT strategies was that the detection threshold was greater with pooling than with individual specimen testing. However, the LoD of the postenrichment pooled NAAT is comparable to the LoD of other described inhouse and commercial PCRs for STEC detection (21)(22)(23). To overcome any potential loss of detection, it may be possible to make method improvements, such as by concentrating enriched pools with centrifugation prior to lysis.…”
Section: Discussionsupporting
confidence: 60%
“…A limitation of the two pooled NAAT strategies was that the detection threshold was greater with pooling than with individual specimen testing. However, the LoD of the postenrichment pooled NAAT is comparable to the LoD of other described inhouse and commercial PCRs for STEC detection (21)(22)(23). To overcome any potential loss of detection, it may be possible to make method improvements, such as by concentrating enriched pools with centrifugation prior to lysis.…”
Section: Discussionsupporting
confidence: 60%
“…The C T values of 9 replicates indicated that the assay was highly reproducible. Multiplex PCRs targeting the major virulence genes (stx 2 , aggR, and aggA) of these strains were used in association with those associated with the somatic (rfb O104 and wzx O104 ) and H4 flagellar (fliC H4 ) antigens (4,12,21,26). In this study, the PCR assays targeting the O104 antigen sequences tested positive for all E. coli O104 strains having H types other than H4 and showed crossreactivity with E. coli strains carrying the K9 capsular antigen and thus were not specific to the O104:H4 strains.…”
Section: Resultsmentioning
confidence: 99%
“…The used PCR assays (4,12,21,26) combine multiple pairs of primers targeting, for example, genes encoding Shiga toxin 2 (stx 2 ), O104 (rfb O104 ) and H4 (fliC H4 ) antigens, tellurite resistance (terD), and AggR (aggR), which is the master regulator of EAEC plasmid, as well as chromosomally inherited virulence genes (18). However, none of these gene targets was unique to the O104:H4 outbreak strain.…”
mentioning
confidence: 99%
“…The number of strains and the diversity of serotypes and pathogroups that were investigated in this study provide a solid base for a future utilization of the CRISPR real-time PCR tests not only on pure bacterial isolates but also on food and stool samples. These assays would work potentially with DNA extracted from enriched food (19) or stool samples (26) suspected to be positive. This needs to be confirmed with further evaluation of the CRISPR PCR tests on spiked and naturally contaminated samples.…”
Section: Discussionmentioning
confidence: 99%